Analisis Yuridis Penetapan Biaya Layanan pada Transaksi Pinjaman Online Perspektif Maqashid Syariah: Studi Kasus pada Fintech Adakami - Zulfan Baihaqi; Mustapa Khamal Rokan (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to determine the legal provisions from the perspective of maqashid sharia in providing legal certainty regarding the determination of service fees on online loan applications. This research takes a normative juridical approach. This type of research is field research. Field research is a type of research that studies phenomena in their natural environment. For this reason, the primary data is data originating from the field (quoting CNBC news media). Then for secondary data from various sources, such as court decisions, laws, regulations, books in personal collections and libraries, newspaper and magazine articles, online journals, and scientific papers. This research shows that determining service fees in online loans requires an understanding of factors such as loan limits, payment tenor and fee structure. OJK regulations and AFPI supervision regulate online lending practices, with a focus on consumer protection and fairness. The Maqashid Sharia view also influences fee setting, emphasizing fairness and prevention of exploitation.